Nuclear magnetic moment studies of short–lived excited states at the edge of the island of inversion: the IS628 experiment - Khaliel, A.; Papaioannou, D.; Zagoraios, G.; Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2019)
Nuclear gfactors are highly sensitive to the single–particle aspects of the wave function, revealing important information for the nuclear structure along the isotopic chart. The sdshell has been thoroughly studied, resulting in “universal” shell model Hamiltonians [1] and the development of an M1 operator [2]. However, there is still shortage of precise experimental gfactor data of excited states to consolidate the nuclear structure in this regime. Recently, the Time Differential Recoil in Vacuum (TDRIV) experimental technique was revamped to be applicable for radioactive beams. TDRIV has been tested successfully and produced high-precision results for the stable 24Mg nucleus [3]. However, the successful application of the technique relies heavily on calibrations of the de–orientation phenomenon. A recent experiment using the MINIBALL array at REX/ISOLDE (IS628) has focused on the application of the method with a radioactive 28Mg beam. The gfactor of the 28Mg first 2+excited state can act as an excellent probe of the N=16 shell gap and the νd3/2singleparticle energy, as well as the possible presence of spdfadmixtures. The particular measurement will be a next step towards a gfactor measurement on 32Mg in the center of the “island of inversion”, where the N=20 shell closure breaks down enhancing 1p–1h excitations and shape–coexistence. In this work, the analysis of the spectroscopic data recorded for a 22Ne beam, which was used for calibrating the experimental method before the actual run on 28Mg is reported. Preliminary data on the angular distributions for the 22Ne 21+→ 0+transition will be presented, an important prerequisite before a remeasurement of g(22Ne;21+).